Ensuring education is not one-legged: spirituality as its essential constituent - Kontrimienė, Simona (Acta Paedagogica Vilnensia, 2019)
[full article and abstract in Lithuanian; abstract in English] The science of education recognises the fusion of cognitive and spiritual development, but conceptions of spirituality vary herein: spirituality is often viewed as authenticity, the process of continually transcending one’s current locus of centricity as well as connectedness and recognition of the higher power that illuminates the meaning of human existence; spirituality may also implicate a critical view, which serves as a counterbalance to traditional religiousness, or an independent being in the world and transrational experiences. In Lithuania, the phenomenon of spirituality is often conceptualised as a person‘s adequate relationship with the world based on fundamental spiritual values (Jovaiša, 2011; Bitinas, 2000; Aramavičiūtė, 2005, 2010; Martišauskienė, 2004; 2011), and its development is closely tied with moral, aesthetic and religious education. The system of internalized spiritual values determines true, belief-inspired knowledge, which is critical in the advancement of spirituality. Importantly, education of spirituality helps to achieve transcendence, an essential component of spirituality which implies belief in the supernatural reality and an ability to transcend the self and shape a holistic view of the world. In institutions of higher education such education may be enabled through three types of activities (White, 2006): (1) academic curricular activities (students’ mind/body connection), (2) reflective time and space (students’ spirituality “within”) and (3) social servant action (students’ spirituality “without”).